Effect of TiO2 addition on Al2TiO5 (tialite) phase evolution of in situ MgAl2O4 formation zero cement castable (ZCC) - Kalpakli, Y. (TAYLOR & FRANCIS LTD, 2014)
In this study, densification behaviour of the in situ MgAl2O4 formation zero cement castable (ZCC) in the presence of TiO2 was analysed. Using a 2 wt-% content of TiO2 increased the bulk density of the brick to 3.10 g cm(-3) and decreased the porosity to similar to 15.7%. Alternatively, a 2 wt-% TiO2 addition modified the firing shrinkage. X-ray diffraction (XRD) analysis of the fired samples demonstrated that MgAl2O4 spinel and Mg2TiO4 inverse spinel structures also formed, as well as the formation of Al2TiO5 in 2 wt-% TiO2 addition of castables. The SEM investigations of fired samples were carried out to compare the effect of TiO2 addition and in situ phase formation on the physicomechanical properties of castables. The effect of TiO2 content on the mechanism of the slag penetration of ZCC for a steel ladle was examined, and the penetration layer was chemically analysed.
Keywords: Electron microscopy; X-ray diffraction; Mechanical characterisation; In situ spinel; Al2TiO5 (tialite); Slag penetration; THERMAL-EXPANSION; MICROSTRUCTURE; CERAMICS; REFRACTORIES; PARAMETERS; CORROSION; MECHANISM; Materials Science